2020
DOI: 10.2319/062520-586.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of mini-screw–assisted rapid palatal expansion on airway:

Abstract: Objectives To evaluate the long-term effects on airway in patients with mini-screw–assisted rapid palatal expansion (MARPE), rapid palatal expansion (RPE), and controls with three-dimensional cone-beam computed tomography (CBCT) analysis. Materials and Methods A total of 180 CBCTs of 60 patients were analyzed at different time points, such as pretreatment, postexpansion, and posttreatment. Patients were divided into three gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 21 publications
5
23
1
3
Order By: Relevance
“…13,14 In some studies, the distance between the central fossa of maxillary first molars has been used to define the maxillary intermolar width. 8 Regardless of the method used for measurement, the difference between the pre-treatment and post-expansion are used to calculate the amount of the expansion. Nada et al performed a study in 2012 on patients who underwent surgical procedure for expansion of maxilla and observed that there was an increase of 5.64 mm +/-2.9 mm in the intermolar width after expansion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 In some studies, the distance between the central fossa of maxillary first molars has been used to define the maxillary intermolar width. 8 Regardless of the method used for measurement, the difference between the pre-treatment and post-expansion are used to calculate the amount of the expansion. Nada et al performed a study in 2012 on patients who underwent surgical procedure for expansion of maxilla and observed that there was an increase of 5.64 mm +/-2.9 mm in the intermolar width after expansion.…”
Section: Resultsmentioning
confidence: 99%
“…MARPE appliances are a relatively newer option for the correction of posterior crossbite and can be used to achieve higher amount of skeletal expansion of maxilla than conventional RPE. 8,9,10 Different devices using mini-implants and maxillary expansion have been reported in the literature. 11 This review will describe the changes achieved with conventional RPE, SARPE, and MARPE.…”
Section: Issn: 2706-6495mentioning
confidence: 99%
“…The changes achieved with MARPE are found to be stable over time. In a recent study, Mehta et al showed that MARPE appliances led to an increased nasopharyngeal volume after 2.5 years following expansion [3] . However, there were no differences in the total airway volume between MARPE and controls.…”
Section: Mini-implants and Maxillary Expansionmentioning
confidence: 99%
“…Thus, the use of palatal mini-implants have increased in past few years [3] . The failure rates of mini-implants are in the low range of 10 to 30 percentage [1,7,8] .…”
Section: Application Of Mini-implants In Orthodonticsmentioning
confidence: 99%
See 1 more Smart Citation